THE CORRELATION BETWEEN LEARNING INDEPENDENCE AND STUDENTS LEARNING RESULT IN CHEMISTRY THROUGH THE IMPLEMENTATION OF DISCOVERY LEARNING MODEL ON SALT HYDROLYSIS TOPIC IN MAN 2 SAMARINDA ACADEMIC YEAR 2014/2015 - Nurlaili -; Awalus Sarifah (PROSIDING SEMINAR KIMIA, 2015)
Learning independence is related to self-management to achieve learning goals, including learning result. One of the learning models which demands students learning independence is the discovery learning. This study aims to: (1) to measure the students level of chemistry learning independence through the implementation of discovery learning model, (2) to determine students learning result through the implementation of discovery learning model on salt hydrolisis topic, (3) to determine positive correlation between learning independence and students learning result in chemistry through the implementation of discovery learning model on salt hydrolisis topic in MAN 2 Samarinda, academic year 2014/2015.This study is classified as associative research. The population of this study is the whole students of MAN 2 Samarinda, while the sample is class XI Science I, whose number is 31 students. The sample is determined by using purposive sampling method. The learning independence data is obtained from learning independence questionnaire, adapted from assessing academic self-regulated learning and students learning result in chemistry is obtained from post-test and regular quiz. The data then analysed by using Pearson’s product moment correlation. The result showed the students learning independence in percentage as follows: highly independent (12.90%), independent (51.61%), fairly independent (35.48%), less independent (0%) and not independent (0%). The learning results percentage are as follow: very high (9.67%), high (19.35%), medium (51.56%), low (19.35%) and very low (0%). There is a positive correlation between learning independence and learning result on medium level (0.433).